2001
DOI: 10.1159/000056350
|View full text |Cite
|
Sign up to set email alerts
|

Dithranol and Dimethylfumarate Suppress the Interferon-γ-Induced Up-Regulation of Cytokeratin 17 as a Putative Psoriasis Autoantigen in vitro

Abstract: In psoriasis an etiopathogenetic vicious circle has been hypothesized in which disease manifestation is triggered by skin-specific autoantigen structures. Autoreactive T cells are supposed to mediate inflammation and hyperproliferation in the epidermopapillary compartment, positively feeding back the expression and accessibility of decisive antigen structures. Recently an epitope within cytokeratin 17 (K17) has been described as such a putative psoriasis autoantigen, which is moreover known to be up-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In the cell culture model of human HaCaT keratinocytes, we investigated by immunoflow cytometry to what extent K17 as a putative psoriasis major autoantigen might be induced on the protein level by cytokines other than IFN-Á known to be crucially involved in the psoriatic disease mechanisms [16][17][18][19]. Such an induction was not detectable for IL-1·, IL-1ß, IL-6, IL-8 and IL-18, but for TNF-· and TGF-·, however only when used in relatively high concentrations of 1,000 and 610 ng/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cell culture model of human HaCaT keratinocytes, we investigated by immunoflow cytometry to what extent K17 as a putative psoriasis major autoantigen might be induced on the protein level by cytokines other than IFN-Á known to be crucially involved in the psoriatic disease mechanisms [16][17][18][19]. Such an induction was not detectable for IL-1·, IL-1ß, IL-6, IL-8 and IL-18, but for TNF-· and TGF-·, however only when used in relatively high concentrations of 1,000 and 610 ng/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was performed as previously described [19]. Briefly, 1 day after plating, subconfluent HaCaT keratinocytes were incubated with IFN-Á at a concentration of 25 U/ml for 72 h. Harvested cells were washed twice with PBS, fixed with 4% paraformaldehyde for 7 min and washed again.…”
Section: Exposure To Ifn-á and K17 Immunoflow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous dermatopathologic research, it has been shown that IFN-can induce apoptosis in HaCAT cells in vitro [19] and increase the expression of K17, which makes it a globally acceptable mimic model of psoriasis [8,19]. In the present study, we evaluated the IFN-induced of apoptosis in HaCAT cells and the expression of K17, both in the presence and the absence of AF-FD.…”
Section: Introductionmentioning
confidence: 91%
“…It has been shown that IFN-can increase the expression of K17 in a human keratinocyte cell line (HaCAT) [6,7]. Some authors used an IFN-/K17 loop to explain the positive feedback mechanism between IFN-activity and K17 expression in psoriasis [8].…”
Section: Introductionmentioning
confidence: 99%